Regions and Regional Uneven Development Forever? Some Reflective Comments upon Theory and Practice. - Hudson, R. (Regional Studies, 2007)
In recent years, for a variety of reasons, there has been a resurgence of interest in 'the region' from a variety of both intellectual and practical perspectives, with the somewhat surprising result that regional studies have come to be of central concern and the region has come to occupy a central place in social scientific discourse and political debates. In this, questions of power loom large. This paper examines four, to a degree inter-weaving, sets of key questions, framed by a concern with who has the power of decision, in both intellectual debates about regions and regional policy and practice. First, how is the region to be defined? Secondly, how can the concept of governmentality deepen one's understanding of regions? Thirdly, how are 'the region's interests' to be defined? And finally, how is regional economic development to be defined? Problematizing what is meant by the terms 'region' and 'development' in these ways and posing and exploring questions such as these will allow the study of regions to be taken forward in a progressive manner in the future.
EPrint Processing Status: Full text deposited in DRO
Keywords: Regions; Regional uneven development; Power; Political economy; Governmentality; Theory and practice.